The performance of third-party funds, consumption credit and profitability - Herry Achmad Buchory; RA. Dwi Utami Widyawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Banks are financial institutions that can collect and distribute funds directly to the public for profit. In carrying out these functions and objectives, the bank has a strategy of raising funds and distributing credit. The purpose of this study was to determine the effect of Third-Party Fund Performance, and Consumption Credit on Profitability. The research method used is descriptive and verification methods with a quantitative approach with a sample of 28 units of secondary data. The data analysis technique used is multiple linear regression. The results of the research analysis show that partially Third-Party Funds have no significant effect on Return on Assets (ROA); Cost of Funds has a significant effect on ROA and Consumption Credit has no significant effect on ROA. Simultaneously Third-Party Funds, Cost of Funds, and Consumption Credit have a significant effect on ROA.